Sustainable transport indicators in the context of introducing of electric passenger cars - Kjosevski, Stevan (Array, 2020)
Sustainable development and sustainable transport are becoming of higher and higher importance. A scientific approach to sustainable development analysis means, first of all, identification of relevant indicators. Based on literature review and regional professionals’ view, a total of 90 indicators have been chosen. They have been structured in five hierarchic levels. A total of five personal transport means alternatives have been analyzed in the research. The AHP method of analysis has been employed in which 75 professionals from the Western Balkan countries have filled appropriate questionnaire. The research presents their opinion about the capacity of each of the alternatives to contribute to the sustainable transport in the region, but also puts a light on perception of the professionals on importance of chosen indicators. The results of this research could be used for further research and could also help to decision making levels regarding sustainable transport and sustainable development.